To Evaluate The Role of Tamra Patra on Changing The Quality Of Drinking Water - Gupta, Sanjay Kumar; Acharya, Pravanjan; Goran, Arif Khan; Bhanot, Neha (International Research Journal of Ayurveda & Yoga, 2021)
From the time immemorial, man has been interested in trying to control disease. Long and healthy life is the basic need of human being to attain the Dharma (righteousness, moral values), Artha (prosperity, economic values), Kama (pleasure, love, psychological values) and Moksha (liberation, spiritual values). i.e. the Chaturvarga. Disease or ill health is the main impediment to achieve this goal. The need of Ayurveda is to promote and preserve health of the healthy person and to restore health when it is impaired. According to Ayurveda, these determining factors are Dincharya (daily regimen), Ratricharya (night regimen), Ritucharya (seasonal regimen) And Sadvritta (code of conduct) etc. Safe water is fundamental to better health, alleviating poverty and community development. The aim of this study was to look into the facts surrounding the traditional use of Tamra Patra (copper vessel) for water storage and to assess its function in changing the quality of drinking water. In this study effect of Copper in purification of drinking water.